Nanoscale design of polarization in ultrathin ferroelectric heterostructures - Gabriele De Luca (Nature Portfolio, 2017)
Ferroelectric heterostructures exhibit a range of functional properties; however control of their growth remains a challenge. De  Luca et al., demonstrate in-situ optical second harmonic generation to monitor and tailor the polarisation and growth of multilayer barium titanate and bismuth ferrite films.